Lumbopelvic motor control and low back pain in elite soccer players: a cross-sectional study. Issue 11 (2nd June 2016) - Grosdent, Stéphanie; Demoulin, Christophe; Rodriguez de La Cruz, Carlos; Giop, Romain; Tomasella, Marco; Crielaard, Jean-Michel; Vanderthommen, Marc
ABSTRACT: This study aimed to investigate the relationship between the history of low back pain and quality of lumbopelvic motor control in soccer players. Forty-three male elite soccer players (mean age, 18.2 ± 1.4 years) filled in questionnaires related to low back pain and attended a session to assess lumbopelvic motor control by means of five tests (the bent knee fall out test, the knee lift abdominal test, the sitting knee extension test, the waiter's bow and the transversus abdominis test). A physiotherapist, blinded to the medical history of the participants, scored (0 = failed, 1 = correct) the performance of the players for each of the tests resulting in a lumbopelvic motor control score ranging from 0 to 5. Forty-seven per cent of the soccer players reported a disabling low back pain episode lasting at least two consecutive days in the previous year. These players scored worse lumbopelvic motor control than players without a history of low back pain (lumbopelvic motor control score of 1.8 vs. 3.3, P < 0.01). The between-groups difference was particularly marked for the bent knee fall out test, the knee lift abdominal test and the transversus abdominis test ( P < 0.01). In conclusion, most soccer players with a history of low back pain had an altered lumbopelvic motor control. Further research should examine whether lumbopelvic motor control is etiologically involved in low back pain episodes in soccer players.